Lying in wait: the resurgence of dengue virus after the Zika epidemic in Brazil - Anderson F. Brito; Laís Ceschini Machado; Márcio Junio Lima Siconelli; Rachel J. Oidtman; Joseph R. Fauver; Rodrigo Dias de Oliveira Carvalho; Filipe Zimmer Dezordi; Mylena Ribeiro Pereira; Luíza Antunes de Castro-Jorge; Elaine Cristina Manini Minto; Luzia Márcia Romanholi Passos; Chaney C. Kalinich; et al. (2020)
Abstract After Zika virus (ZIKV) emerged and caused an epidemic in the Americas in 2016, both Zika and dengue incidence declined in the following years (2017-2018) to a record low in many countries. Following this period of low incidence, dengue resurged in 2019 in Brazil, causing ~2.1 million cases. The reasons for the recent fluctuations in dengue incidence and the maintenance of dengue virus (DENV) through periods of low transmission are unknown. To investigate this, we used a combination of epidemiological and climatological data to estimate dengue force of infection (FOI) and model mosquito-borne transmission suitability since the early 2000s in Brazil. Our estimates of FOI revealed that the rate of DENV transmission in 2018-2019 was exceptionally low, due to a low proportion of susceptible population rather than changes to ecological conditions. This supports the hypothesis that the synchronous decline of dengue in Brazil may be explained by protective immunity from pre-exposure to ZIKV and/or DENV in prior years. Furthermore, we sequenced 69 genomes of dengue virus serotype 1 (DENV-1) and DENV-2 circulating in Northeast and Southeast Brazil, and performed phylogeographic analyses to uncover patterns of viral spread. We found that the outbreaks in Brazil in 2019 were caused by DENV lineages that were circulating locally prior to the Zika epidemic and spread cryptically during the period of low transmission. Despite the period of low transmission, endemic DENV lineages persisted for 5-10 years in Brazil before causing major outbreaks. Our study challenges the paradigm that dengue outbreaks are caused by recently introduced new lineages, but rather they may be driven by established lineages circulating at low levels until the conditions are conducive for outbreaks.